Paulo Freire: His Thoughts on Adult Education - Pratap, Raghvendra Krishna (JOURNAL OF INDIAN EDUCATION, 2011)
The present article focuses on the development of Paulo Freire as an adult educator and an educational thinker. For his views and practices he was arrested and exiled in March 1964 by the military government of Brazil, and could only return in 1980. In the mean time he was working as an advisor to World Congress of Churches. During 1980-1988 he was made in charge of Adult Education projects of Workers’ Party. In 1988 he was appointed Minister of Education.The key features of Freirean approach are ‘dialogue’ and ‘problem solving’. For native language literacy, words are selected showing the most important concerns of the people. The literacy training is provided through three sub-stages: motivational sessions , development of teaching material and literacy training (de-codification). Of course the scholars and workers in the field of adult education, have shown several flaws in his approach.